HIGH ETICAL CONDUCT OF ENGINERS AS A VERITABLE TOOL FOR NATIONAL ECONOMIC ADVANCEMENT - NDUBUISI , PROF. OKEKE GERALD; ENGR. PROF. SONY EMEKA ALI; DR OMATSEYIONE NESIAMA; ENGRCLETUS ONYEMHESEAGBAKHAMEN; ASSOCIATE PROFESSOR CYNTHIA AMAKAOBIORAH PHD; ENGR UGAH THEOPHILUS AKU (IPHO-Journal of Advance Research in Science And Engineering, 2025)
Professionally accepted standards of personal and business behaviour, values and guiding principles. Codes of professional ethics are often established by professional organizations to help guide members in performing their job functions according to sound and consistent ethical principles (Web Finance Inc., 2020). Tutorialspoint (2020) opine that: Ethics has its origin in the Greek word “ethos”, which means “character”. Thus ethics are a set of principles or rules generally considered as standards good or bad, right and wrong, usually imposed by a profession, society, regulatory body or even an external group. Engineering ethics involves the decisions, policies and values that are morally desirable in engineering practice and research. Aside moral issues, engineering ethics include but not limited to responsibility for safety, confidentiality, balanced outlook on law of the land/international law, global issues, professionalism etc. The word best practices often refer to the standard acceptable in a profession worldwide. Juxtaposing the above with engineering itself being a process of developing efficient mechanism which eases and quickens the work in regards to limited resources and the help of technology. Cutting edge technology therefore, permit me to say, enjoys the confidence of professional ethics.